Cooperative Learning Model of the Picture and Picture Type Assisted by the Traditional Sepit-Sepitan Game on the Responsibility Character of Fourth-Grade Elementary School Students - Ni Nyoman Sintya Sukma Dewi; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2025)
The low level of students’ responsibility character, attributed to the dominance of conventional teaching methods, highlights the need for innovative learning models grounded in local culture that can meaningfully instill character values. This study aims to analyze the effect of the Picture and Picture model assisted by the traditional game sepit-sepitan on the responsibility character of elementary school students. A quasi-experimental approach was employed, using a non-equivalent control group design. The study involved 30 students selected through cluster random sampling, consisting of 17 students in the experimental group and 13 in the control group. Data were collected using an observation sheet measuring responsibility character on a dichotomous scale. The data were analyzed using the independent sample t-test. The analysis revealed that tcount = 2.90 exceeded ttable = 2.048 at the 5% significance level, indicating that H₀ is rejected and H₁ is accepted. These results suggest that the Picture and Picture model assisted by the sepit-sepitan game has a significant positive effect on improving students' responsibility character. The findings imply that the integration of culturally-based learning models can serve as an effective and enjoyable strategy for strengthening character education from an early age.